The Impact of the Competitive Learning Strategy on Receiving and Setting Skills in Volleyball - Yacoub, Mahmoud Hussien; Al-luwaici, Nezar "Mohammed Khiar" (Dirasat: Educational Sciences, 2023)
Objectives: The study aimed to examine the impact of the competitive learning strategy on learning volleyball receiving and setting skills among volleyball course students at Yarmouk University in Jordan. Methods: A quasi-experimental method was employed with a sample of 36 students enrolled in the volleyball course during the first semester of 2021/2022. The participants were selected using the intentional sampling method. The control group received instruction using the usual teaching method, while the experimental group implemented the competitive learning strategy over an eight-week period, with three sessions per week. Skill performance tests were conducted to measure the effectiveness of receiving and setting skills in volleyball. Data analysis involved the use of arithmetic means, standard deviations, frequencies, percentages, and a sample t-test. Results: The results indicated statistically significant differences (p < 0.05) between the pre- and post-measurements of both groups in receiving and setting skills, favoring the post-measurement. Moreover, a statistically significant relationship (p < 0.05) was observed between the use of the usual teaching method and the competitive learning strategy in terms of learning receiving and setting volleyball skills during the post-measurement, with a preference for the competitive learning strategy. Conclusions: The study emphasizes diversifying teaching strategies to match the specific requirements of sports and game skills, focusing on applying volleyball skills in different playing conditions. It recommends adopting the competitive learning strategy for teaching volleyball skills, team sports, and individual games in physical education faculties, public, and private schools.